2010
DOI: 10.1016/j.ultsonch.2009.04.008
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical model for ice primary nucleation induced by acoustic cavitation

Abstract: The modelling and simulation of ice nucleation triggered by acoustic cavitation was addressed in this study. The objective was to evaluate the number of nuclei generated by a single gas bubble and afterwards by a multi-bubble system as function of the acoustic pressure (ultrasound wave amplitude) and supercooling level (liquid temperature). According to our calculations, the nucleation could be initiated with moderated acoustic pressure amplitude (around one bar) even at low supercooling levels (around few deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(37 citation statements)
references
References 22 publications
0
37
0
Order By: Relevance
“…Recently, various methods (alternative to the shelf-ramped freezing) have been proposed to make this process less unpredictable [3][4][5][6][7][8][9][10][11][12][13][14]. Among these include the following: electrofreezing [4], ultrasound [5][6][7][8], depressurization method [9] and ice fog technique [10][11]. All these methods were found to give a dramatic reduction in cycle duration and improve the homogeneity of the batch as a whole, thus ensuring similar product characteristics in all the vials of the batch.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, various methods (alternative to the shelf-ramped freezing) have been proposed to make this process less unpredictable [3][4][5][6][7][8][9][10][11][12][13][14]. Among these include the following: electrofreezing [4], ultrasound [5][6][7][8], depressurization method [9] and ice fog technique [10][11]. All these methods were found to give a dramatic reduction in cycle duration and improve the homogeneity of the batch as a whole, thus ensuring similar product characteristics in all the vials of the batch.…”
Section: Introductionmentioning
confidence: 99%
“…There are three kinds of mechanism of ultrasound induces primary nucleation (Saclier et al, 2010;Kiani et al, 2011). Firstly, the high pressures occurring during the vigorous collapse of transient ultrasonic cavitation bubbles results in high degrees of supercooling.…”
Section: The Dough Freezing Curvesmentioning
confidence: 99%
“…During the phase transition stage, the ultrasonic cavitation bubble provided a favorable condition for the occurrence of heterogeneous primary nucleation of ice, and shock waves and micro-jets promoted secondary nucleation by breaking up the pre-existing dendritic ice crystals into tiny nuclei (Chow et al, 2003(Chow et al, , 2004(Chow et al, , 2005Delgado et al, 2009;Delgado and Sun, 2011;Inada et al, 2001;Kiani et al, 2011Kiani et al, , 2012Petzold and Aguilera, 2009;Saclier et al, 2010;Zhang et al, 2001Zhang et al, , 2003Zheng and Sun, 2006). In Fig.…”
Section: The Effects Of Electrical Power On Freezing Timementioning
confidence: 99%
See 1 more Smart Citation
“…Chow et al (2003Chow et al ( , 2004 reported that ultrasound irradiation showed its ability to initiate nucleation in supercooled aqueous solutions. Saclier et al (2010) and Ruecroft et al (2005) reported that power ultrasound was employed to trigger nucleation in industrial crystallization processes of organic molecules. Therefore, the power ultrasound used to manipulate nucleation and improve the repeatability of the process can be a promising method.…”
Section: Introductionmentioning
confidence: 99%